Capital and innovation aggregation with environmental pressure: An optimal evolution - Feng Dai; Songtao Wu; Ling Liang (Cogent Economics & Finance, 2014)
Based on the advance-retreat course model, a growth model under environmental pressure, this paper builds an economic growth model that focuses on the aggregation of capital and innovation with environmental pressure. Importantly, the paper presents methods for computing the optimal quantity of capital-goods and innovation-goods. The paper makes the empirical researches using US GDP data (1940 - 2010 and 1969 - 2010). The findings include that the aggregations of capital and innovation promote economic growth, the optimal number of capital-goods decreases with innovation growth, the optimal number of innovation-goods decreases with capital expansion, both capital-goods and innovation-goods aggregate with environmental pressure increasing, and innovation is quicker than capital in aggregation.
Keywords: E25; F21; O21; P23; 330; economic growth; environmental pressure; capital-goods; innovation-goods; optimal aggregation